Simple methodology to estimate bioavailability in early clinical studies: theory and reality. (July 2017) - Liu, Lichuan; Liu, Xingrong; Wei, BinQing; Khojasteh, S Cyrus
Aim: We propose a simple methodology to estimate oral bioavailability from Phase I clinical trials, which can be broadly phrased as 'calculated bioavailability' (FCAL ).Materials & methods: FCAL is estimated by obtaining the product of circulating maximal observed drug concentration (Cmax ') and the estimated volume of distribution at steady state (VSS ') followed by dividing this product by the administered dose (d). VSS ' is estimated by allometric scaling based on the preclinical intravenous data.Results & conclusion: Overall, these analyses indicate that when the absorption is faster than elimination process and the VSS ' allometry exponent is between 0.9 and 1.1, the Fcal is a good estimate of the F.